2011
DOI: 10.1007/s11481-011-9287-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-alpha and the Roles it Plays in Homeostatic and Degenerative Processes Within the Central Nervous System

Abstract: Tumor Necrosis Factor-alpha (TNF-α) is a prototypic pro-inflammatory cytokine involved in the innate immune response. TNF-α ligation and downstream signaling with one of its cognate receptors, TNF-RI or TNF-RII, modulates fundamental processes in the brain including synapse formation and regulation, neurogenesis, regeneration, and general maintenance of the central nervous system (CNS). During states of chronic neuroinflammation, extensive experimental evidence implicates TNF-α as a key mediator in disease pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
0
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(216 citation statements)
references
References 199 publications
(199 reference statements)
5
190
0
21
Order By: Relevance
“…In pathophysiological conditions, astrocytes and especially microglia release large amounts of TNF-α (23). An increased level of TNF-α has been reported in disorders such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis (24,25). Morphine binds to μ-opioid receptors in microglia and increases the secretion of inflammatory factors such as TNF-α (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…In pathophysiological conditions, astrocytes and especially microglia release large amounts of TNF-α (23). An increased level of TNF-α has been reported in disorders such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis (24,25). Morphine binds to μ-opioid receptors in microglia and increases the secretion of inflammatory factors such as TNF-α (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, inflammatory cytokines such as interleukin (IL)-1b, IL-6, tumor necrosis factor-α (TNF)-α, reactive oxygen species (ROS) and inducible nitric oxide synthase (iNOS) were elevated in cerebrospinal fluid (CSF) of PD patients. Their elevation has further influence on neurons thus the triggering of advanced neurodegeneration [30,32,33]. Studies [30,34,35] have shown that α-synuclein, the key constituent of Lewy bodies can trigger neurodegeneration in the accumulated form and partake in microglial stimulation by augmented generation of proinflammatory cytokines, thus causing an assiduous and radical nigral neurodegeneration in PD.…”
Section: α-Mg and Microgliamentioning
confidence: 99%
“…These pro-inflammatory cytokines have been investigated mostly for their anti-inflammatory actions. TNF-α has also been suggested to have a key-role in particleinduced inflammation study ( Baune et al, 2012) and it has been concluded that TNF-α can induce an increase in airway responsiveness in healthy subjects, thus making it a cytokine candidate for the induction of airway inflammation and hyper responsiveness (Elahi et al, 2009, Montgomery andBowers, 2012). This research is intended to observe the effects of exposure to selected indoor air pollutants through the reaction of biological samples, which indicate the susceptibility of lung inflammation.…”
Section: Ajasmentioning
confidence: 99%